Proposition and Argument within Class Discussion of Junior High School Students - Narimo Narimo; Anang Santosa; Yuni Pratiwi; Mujianto Mujianto (Jurnal Pendidikan Humaniora, 2015)
Proposisi dan Argumen Dalam Diskusi Kelas Siswa SMPAbstract: This study is to describe and explain the proposition and argument on classroom discussion of Junior High School students. The data are collected through observation techniques with the audio-video cameras supported by field notes to the subjects of this study; 235 students of the eighth grade of SMP Negeri 1 Watulimo Trenggalek, East Java. Data analysis is undertaken using qualitative data analysis by Miles and Huberman. The results of the study are the proposition and the argument on classroom discussion of Junior High School students. The proposition on classroom discussion of Junior High School students are the affirmation or negation propositions expressed by one or more students. The argument on classroom discussion of Junior High School students is the argument constructed by students collaboratively.Key Words: proposition, argument, classroom discussionAbstrak: Penelitian ini bertujuan untuk mendeskripsikan dan menjelaskan proposisi dan argumen dalam diskusi kelas siswa SMP. Data penelitian dikumpulkan melalui teknik observasi dengan bantuan kamera audio video yang didukung oleh catatan lapangan terhadap subjek penelitian sejumlah 235 siswa kelas VIII SMP Negeri 1 Watulimo Kabupaten Trenggalek, Provinsi Jawa Timur. Data yang ter-kumpul dianalisis secara interaktif model Miles dan Huberman. Hasil penelitian ini adalah proposisi dan argumen dalam diskusi kelas siswa SMP. Proposisi dalam diskusi kelas siswa SMP berupa pro-posisi afirmasi atau negasi yang dinyatakan oleh seorang siswa atau lebih. Argumen dalam diskusi kelas siswa SMP berupa argumen yang dibangun siswa secara kolaboratif.Kata-kunci: proposisi, argumen, diskusi kelas